Sexual Violence Against Girls Committed by Next of Kin - Timisela, Victor Riko Febrianko; Sopacua, Margie Gladies (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Sexual violence against children has long-term impacts and reflects systemic failures in protection, especially when perpetrators are family members. Despite existing regulations, cases continue to rise, and victims often remain silent due to social pressure. This study is needed to understand the root causes and develop more effective prevention strategies.Purposes of the Research: This study aims to analyze the contributing factors of sexual violence committed by close family members against children and to examine the efforts made to address the issue.Methods of the Research: The method used is empirical juridical research with a descriptive qualitative approach.Findings of the Research: The research findings reveal that the main factors contributing to sexual violence within families include economic dependence, power dynamics, individual factors, family dysfunction, and socio-cultural influences. Common modus operandi used by perpetrators involve power relations, threats and intimidation, emotional manipulation, normalization of abuse, and creating opportunities for violence. In terms of curative approaches, relevant institutions provide psychological support and rehabilitation, legal aid and advocacy, medical care and recovery, temporary shelters, as well as social reintegration and family support.